A compact microstrip antenna with dual thin slits for high-capacity data streaming in the 38 and 39 GHz bands for 5G applications - Gaid, Abdulguddoos S.A.; Ali, Ala'a N.S.; Alomari, Mohammad Ahmed (Elsevier B.V., 2024)
This article presents a simple rectangular microstrip antenna for 5G applications in the 38 and 39 GHz bands. The antenna prioritizes broad bandwidth and high gain for efficient signal transmission. It features a compact design, printed on a Rogers RT/Duroid 5880 substrate with dimensions of 5 × 8.2 × 0.186 mm3 (εr = 2.2 and tanδ = 0.0009) and includes two thin slits integrated with the radiating patch. This configuration achieved an impressive 3.11 GHz impedance bandwidth, covering a broad spectrum from 37.23 GHz to 40.34 GHz. Additionally, the radiation gain ranges from 6.55 dBi at the band’s upper frequency to 9.03 dBi at the lower frequency, with a value of 9.03 dBi at the primary operational frequency of 38 GHz. The radiation efficiency remains nearly consistent across the operational frequencies, ranging from 86.97 % at the upper end to 88.96% at the lower end, with an efficiency of 88.29 % at 38 GHz. Moreover, the antenna exhibits excellent matching to its feed, as demonstrated by the minimal value of 1.012 for Voltage Standing Waves Ratio (VSWR) and the low S11 parameter value of -60 dB at the 38 GHz frequency. The proposed antenna was designed and optimized using the Computer Simulation Technology (CST) simulator, while its performance was verified with the HighFrequency Structure Simulator (HFSS). The results from both simulators align remarkably well. This antenna design demonstrated promising bandwidth and radiation characteristics, making it well-suited for 5G applications.